Prolyl endopeptidase activity in bronchoalveolar lavage fluid: a novel diagnostic biomarker in a guinea pig model of invasive pulmonary aspergillosis. (August 2013) - Jambunathan, Kalyani; Watson, Douglas S.; Najvar, Laura K.; Wiederhold, Nathan P.; Kirkpatrick, William R.; Patterson, Thomas F.; Askew, David S.; Kodukula, Krishna; Galande, Amit K.
Abstract Improved diagnostics are needed to detect invasive pulmonary aspergillosis, a life-threatening infection caused by the pathogenic fungus Aspergillus fumigatus. We are investigating secreted fungal proteases as novel biomarkers for the diagnosis of this disease. Although the A. fumigatus genome encodes a multitude of secreted proteases, few have been experimentally characterized. Here, we employed an unbiased combinatorial library of internally quenched fluorogenic probes to detect infection-associated proteolysis in the lungs of guinea pigs experimentally infected with A. fumigatus. Comparative protease activity profiling revealed a prolyl endopeptidase activity that is reproducibly induced during infection but is not observed in healthy animals. This proteolytic activity was found in four independent animal experiments involving two A. fumigatus isolates. We synthesized a small, focused fluorogenic probe library to define the substrate specificity of the prolyl endopeptidase substrate motif and to identify optimal Probe sequences. These efforts resulted in the identification of a panel of six individual substrate-based fluorescent probes capable of detecting infection in guinea pigs with high statistical significance (P<0.005 in most cases). Receiver operating characteristic analyses demonstrated that this fluorogenic assay could detect A. fumigatus infection-associated proteolysis with comparable sensitivity and specificity as existing diagnostic procedures, suggesting that further optimization of the methodology may lead to improved diagnostics options for invasive pulmonary aspergillosis.